The Third Space in Postcolonial Architecture: Hybridity and Cultural Resistance in Singaraja - Pande, I Made Artadi; Bagus Udayana, Anak Agung Gde; Wasista, I Putu Udiyana (LP2M ISBI Bandung, 2025)
Situated within the contested terrain of colonial architectural inheritance, this article interrogates domestic hybridity in Singaraja, Bali, as a site of spatial negotiation and epistemic dissent. Mobilizing Homi Bhabha's third space as both an analytic and a method, it explores how local undagi engage neoclassical forms not as passive recipients but as strategic agents of cultural rearticulation. Drawing on ethnographic immersion, architectural typology analysis, and dialogic interviews, ten heritage houses are examined as performative loci where mimicry and subversion intertwine. The study reveals that architectural hybridity emerges less as visual synthesis and more as a tactical disruption of colonial order, a vernacular counter-script enacted through space, symbolism, and ritual. In reframing architecture as a site of indigenous theorizing, the discussion foregrounds postcolonial spatiality not as peripheral to heritage discourse but central to its decolonial reorientation.